2022
DOI: 10.3389/fsurg.2022.908381
|View full text |Cite
|
Sign up to set email alerts
|

Application of 3D Simulation Software in Chemotherapy and Hepatoblastoma Surgery in Children

Abstract: PurposeThis study aims to explore the clinical value of a computer-assisted surgery system (Hisense CAS) in hepatoblastoma (HB) surgery in children after neoadjuvant chemotherapy.Patients and MethodsThe clinical medical records of children with HB treated after neoadjuvant chemotherapy at the Affiliated Hospital of Qingdao University from January 2016 to January 2019 were analyzed retrospectively.ResultsA total of 21 children were enrolled in this study, including 13 boys and 8 girls. All cases successfully un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…CAS is a 3D reconstruction based on CT data that can be used for precise preoperative evaluation and surgical planning by reconstructing organs and tumors and tracking arteries. It can display the adjacent relationship between the tumor and surrounding vascular organs in a 3D, dynamic and overall way[ 17 ]. The CAS of this patient clearly showed that the giant retroperitoneal tumor completely encased the inferior mesenteric artery with a clear vessel shape and normal tube wall shape.…”
Section: Discussionmentioning
confidence: 99%
“…CAS is a 3D reconstruction based on CT data that can be used for precise preoperative evaluation and surgical planning by reconstructing organs and tumors and tracking arteries. It can display the adjacent relationship between the tumor and surrounding vascular organs in a 3D, dynamic and overall way[ 17 ]. The CAS of this patient clearly showed that the giant retroperitoneal tumor completely encased the inferior mesenteric artery with a clear vessel shape and normal tube wall shape.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the CAS‐assisted group experienced less intraoperative blood loss and a lower blood transfusion rate than the control group. The 3D reconstruction image is more clearly illustrates the adjacency between the tumor and the blood vessels, whether it invades the blood vessels, and the variation of the blood vessels when compared to the 2D plane image 12 ,. 14 , 19 Compared with other 3D reconstruction software, 12 , 20 the entire process of 3D reconstruction with the Hisense CAS system takes roughly 20 min, so it takes less time and has higher work efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The 3D reconstruction image is more clearly illustrates the adjacency between the tumor and the blood vessels, whether it invades the blood vessels, and the variation of the blood vessels when compared to the 2D plane image 12 ,. 14 , 19 Compared with other 3D reconstruction software, 12 , 20 the entire process of 3D reconstruction with the Hisense CAS system takes roughly 20 min, so it takes less time and has higher work efficiency. Therefore, it is very suitable for more urgent preoperative planning cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hisense CAS can also display the overall 3D anatomical relationship and pipeline variations in a semitransparent and interactive way, calculate the distance between any two points and the angle of travel of any blood vessel, the range of innervation or drainage, and the volume of organs and tumors, and provide other information that cannot be obtained from traditional 2D images. In addition, a cloud-based 3D visualization platform for precision surgery based on B/S architecture was constructed to realize the data interactions between the PC terminal browser and CAS and to store, manage and share 2D and 3D image data (Figure 1) [8,9].…”
Section: Research and Development Of Cas Based On Artificial Intellig...mentioning
confidence: 99%